Differential tissue-specific damage caused by bacterial epididymo-orchitis in the mouse. (3rd February 2020) - Klein, Britta; Bhushan, Sudhanshu; Günther, Stefan; Middendorff, Ralf; Loveland, Kate L; Hedger, Mark P; Meinhardt, Andreas
Abstract: Ascending bacterial urinary tract infections can cause epididymo-orchitis. In the cauda epididymidis, this frequently leads to persistent tissue damage. Less coherent data is available concerning the functional consequences of epididymo-orchitis on testis and caput epididymidis. This in vivo study addresses the functional and spatial differences in responsiveness of murine epididymis and testis to infection with uropathogenic Escherichia coli (UPEC). Whole transcriptome analysis (WTA) was performed on testis, caput, corpus and cauda epididymidis of adult C57BL/6 J wildtype mice. Following UPEC-induced epididymo-orchitis in these mice, epididymal and testicular tissue damage was evaluated histologically and semi-quantitatively at 10 days and 31 days post-inoculation. Expression of inflammatory markers and candidate antimicrobial genes were analysed by RT-qPCR. WTA revealed distinct differences in gene signatures between caput and cauda epididymidis, particularly amonst immunity-related genes. Cellular and molecular signs of testicular inflammation and disruption of spermatogenesis were noticed at day 10, but recovery was observed by day 31. In contrast to the cauda, the caput epididymidis did not reveal any signs of gross morphological damage or presence of pro-inflammatory processes despite confirmed infection. In contrast to beta-defensins, known UPEC-associated antimicrobial peptides (AMP), like Lcn2, Camp and Lypd8, were inherently highly expressed or upregulated in the caput following infection, potentially allowing an early luminal protection from UPEC. At the time points investigated, the caput epididymidis was protected from any obvious infection/inflammation-derived tissue damage. Studies addressing earlier time-points will conclude whether in the caput epididymidis a pro-inflammatory response is indeed not essential for effective protection from UPEC.